Multiphase modeling of the DC plasma–water interface: application to hydrogen peroxide generation with experimental validation. (1st July 2022) - Keniley, Shane; Uner, Necip B; Perez, Elizabeth; Sankaran, R Mohan; Curreli, Davide
Abstract: Here, we present a one-dimensional, time-dependent multi-physics model of a plasma–liquid interface that encompasses both the plasma and liquid phases using the MOOSE-based drift–diffusion–reaction software, Zapdos-Crane. The model was applied to an experimental configuration comprised of a direct-current powered argon plasma formed at the surface of an aqueous, ionically conductive solution. In this system, one of the reactions that occurs is the formation of hydroxyl radicals, which subsequently produce hydrogen peroxide. We studied potential mechanisms for hydrogen peroxide production with the plasma operated as either the cathode or anode. Experiments were performed in support of modeling to characterize the plasma and measure the aqueous hydrogen peroxide, and both modeling and experimental results show that its production is substantially higher during anodic operation. In the case of the cathodic plasma, the simulations predict that solvated electrons degrade aqueous hydrogen peroxide, and in support, adding nitrate, a known electron scavenger, to the electrolyte during cathodic operation is shown to increase the production of aqueous hydrogen peroxide by an order of magnitude in experiments.